Discourse Analysis of Teenagers' Language Police on Tiktok Social Media - Nirmala Alyas; Armianti Syah; Arini Junaeny (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This study examines language politeness among adolescents in TikTok comment sections as a form of dynamic and expressive digital communication. The purpose of this research is to analyze the politeness strategies used by adolescents in online interactions based on Brown and Levinson’s politeness theory. This study employs a qualitative approach using discourse analysis methods. The data consist of words, phrases, and sentences collected from comments on TikTok content widely accessed by adolescents. Data were collected through observation, note-taking, and documentation techniques, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that positive politeness is the most dominant strategy, realized through explicit compliments, support and motivation, the use of familiar address terms, and the intensification of emotional expressions through capitalization, word elongation, and emojis. Additionally, limited use of off-record strategies was found, while negative politeness and bald-on-record strategies were not identified. These findings indicate that adolescent interactions on TikTok tend to be supportive and oriented toward strengthening social solidarity Keywords: Language Politeness; Teenagers; Social Media; Tiktok; Discourse Analysis